Some Aspects of Pituitary-Adrenal and Autonomic Nervous Systems Functioning in Patients with Chronic Consciousness Disorders - G. Yu. Rybakov; E. A. Kondratyeva; L. M. Tsentsiper; A. A. Denisova; N. V. Dryagina; N. A. Lesteva; A. O. Ivanova; A. N. Kondratyev (Вестник анестезиологии и реаниматологии)
Patients with chronic disorders of consciousness (CDoC) have various variants of the pathological organization of functions including sympathetic hyperactivity and hormonal changes.The objective: to determine the severity of paroxysmal sympathetic hyperactivity (PSH), the function of the pituitary-adrenal system in patients with CDoC.Subjects and Methods. 54 patients with CDoC were enrolled in the study. Patients were randomized in the groups depending on assessment on the Coma Recovery Scale-Revised scale and CRS-R index calculation. PSH severity was assessed 7 times a day for two days. During the first week from the moment of admission, blood sampling was performed 7 times a day to study the levels of ACTH and cortisol.Results. PSH syndrome was detected in all groups, there were no significant dependencies of its severity on the time of day. There were no significant differences in the levels of ACTH and cortisol during the day.Conclusions: PSH syndrome is observed in most patients with CDoC. In patients with CDoC, the daily rhythm of ACTH and cortisol secretion are disrupted.